Pulmonary histoplasmosis simulating metastasis: two cases report and review of the literature - Artur S. Azevedo; Nábia Maria M. S. Simão; Ricardo M. C. Azevedo; Frederico P. Barbosa (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction and objectives: Systemic mycoses are of great importance in immunosuppression-associated conditions. Histoplasmosis can produce different symptoms that may simulate metastasis. We aim to demonstrate the importance of histopathological confirmation of lesions suggestive of metastases in patients with malignant neoplasm. Cases report: Two patients undergoing cancer treatment, whose chest computed tomography (CT) revealed pulmonary nodules, compatible with metastases. The lesions were biopsied, confirming histoplasmosis granuloma. Conclusion: In patients with cancer, clinical and radiological findings are not limited to metastatic dissemination of tumors, requiring histopathological confirmation of lesions suggestive of metastasis, excluding other diseases and preventing inappropriate treatment.